2019
DOI: 10.1016/j.physa.2019.03.093
|View full text |Cite
|
Sign up to set email alerts
|

Nonextensive triplets in stock market indices

Abstract: Stock market indices are one of the most investigated complex systems in econophysics.Here we extend the existing literature on stock markets in connection with nonextensive statistical mechanics. We explore the nonextensivity of price volatilities for 34 major stock market indices between 2010 and 2019. We discover that stock markets follow nonextensive statistics regarding equilibrium, relaxation and sensitivity. We find nonextensive behavior in stock markets for developed countries, but not for developing c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The quantity defined by equation ( 20) is known as the q-distance between two q-triplets and has been used before in financial systems (for example in Stosic, 2019) to describe differences between the extensive statistics of two distinct timeseries.…”
Section: Generalized Hurst Exponent (Hq)mentioning
confidence: 99%
See 1 more Smart Citation
“…The quantity defined by equation ( 20) is known as the q-distance between two q-triplets and has been used before in financial systems (for example in Stosic, 2019) to describe differences between the extensive statistics of two distinct timeseries.…”
Section: Generalized Hurst Exponent (Hq)mentioning
confidence: 99%
“…In this direction, Stosic et al (Stosic, 2019) studied the non-extensivity of price volatilities for 34 major stock market indices between 2010 and 2019 by the estimation of q-triplet of Tsallis statistics. The distances between q-triplets [2] indicated that some stock markets might share similar non-extensive dynamics, while others are widely different.…”
Section: Introductionmentioning
confidence: 99%
“…A key innovation of our approach lies in the discovery of a general statistical distribution governing limit order cancellation times. We propose the application of Tsallis statistics, a generalization of Boltzmann-Gibbs statistics [30][31][32], to fit the histograms of limit order cancellation times. Remarkably, the distribution's parameters for various stocks and time periods appear close, suggesting a universal nature of the observed statistical property.…”
Section: Introductionmentioning
confidence: 99%